Cutaneous Squamous Cell Carcinoma in Solid Organ Transplant Patients - Leandro Silva; João Borges-Costa (Sociedade Portuguesa de Dermatologia e Venereologia, 2020)
Solid organ transplant recipients (SOTR) are more likely to develop cutaneous squamous cell carcinoma (CSCC), compared to the general population. This increased incidence is due to several factors including chronic ultraviolet radiation exposure, human papillomavirus (HPV) infection, immunosuppressive medication, among others. Primary prevention is crucial, because not only are cutaneous squamous cell carcinomas more frequent in SOTR, but they are also more aggressive and have therefore a worse prognosis. Newer immunosuppressive drugs are associated with a smaller risk of developing CSCC, but they can have more adverse events, prompting patients to abandon therapy. Concerning treatment options for CSCC, they range from surgery, radiotherapy, and systemic therapy, although there are few studies in SOTR concerning the use of immunotherapy and epidermal growth factor receptor (EGFR) inhibitors.